Test the Cytotoxicity of Pleurotin Extracted from an Edible Mushroom Pleurotus osteratus Against Three Human Carcinoma Cell Line - Al-Temimay, Israa A.; AL-Jibouri, Muna H.; A. Hassan, Abdulla; Mohammad, Farooq I. (Iraqi Journal of Science, 2023)
The study included selection six species of the fungi related to Pleurotus genus were evaluated for their ability to production of Pleurotin, one of them, Pleurotus ostreatus (P.11) was isolated and identified in the present study. Pleurotin was extracted with screening by Thin Layer Chromatography (TLC) and quantification High Performance Liquid Chromatography (HPLC). Cytotoxicity of Pleurotin extracted from P. ostreatus (P.11) grown in different sugar sources (galactose, mannitol, sucrose, dextrose and lactose) liquid media was test against three selected cancer cell lines, CaSki, MCF-7 and A549 addition to Human Non Cancer Fibroblast Cell Line (MRC-5). Pleurotin of P. ostreatus (P.11) grown in galactose induced the significant highest growth inhibition against all three cancer cell lines MCF-7 CaSki, and A549 at 72 h treatment period with IC50 29.84 ± 2.37, 30.25 ± 2.40 and 37.60 ± 2.65 μg/ml respectively when the P≤0.01, while it showed no adverse effect on the non-cancer human fibroblast cell line MRC-5 with IC50 >200 μg/ml. Cytotoxicity of Pleurotin was compared with cytotoxicity of the positive controls (chemotherapeutic drugs) including Doxorubicin against CaSki and A549 cell lines and Cisplatin against MCF-7 and MRC-5 cell lines, although IC50 of pleurotin was higher (30.25 ± 2.40 and 37.60 ± 2.65 μg/ml) than Doxorubicin (0.18 ± 0.00 and 1.10 ± 0.02 μg/ml) of CaSki and A549 cell lines, respectively, and also IC50 of Pleurotin was higher (29.84 ± 1.73 and >200 μg/ml) than Cisplatin (8.20 ± 0.25 and 8.88 ± 0.13 μg/ml) of MCF-7 and MRC-5 cell lines, respectively, pleurotin was natural product from an edible fungus while Doxorubicin and Cisplatin were chemical drugs.